Understanding architecture : its elements, history, and meaning - Roth, Leland M.; Clark, Amanda C. R., 1977- (2014)
"This bestselling, illustrated survey of Western architecture is now fully revised throughout, explaining the structure, function, history, and meaning of architecture in a way that is both accessible and engaging. The long-awaited third edition includes increased global coverage with new mini chapters on Africa, Japan, China, India, and Islamic Architecture; a new chapter covering the future of architecture in the twenty-first century; updated coverage of sustainability and green architecture and its impact on design; an update to the historical survey; and over fifty images in full color. Understanding Architecture continues to be the only text in the field to examine architecture as a cultural phenomenon as well as an artistic and technological achievement with its straightforward, two-part structure: (1) The Elements of Architecture and (2) The History and Meaning of Architecture. Comprehensive and clearly written, Understanding Architecture is a classic survey of Western architecture. "--
The Elements of Architecture -- The History and Meaning of Architecture.
Includes bibliographical references (pages 669-683) and index.
Keywords: Architecture; Architecture -- History; ARCHITECTURE / General; ARCHITECTURE / History / General; ARCHITECTURE / Buildings / General; ARCHITECTURE / Criticism